AAPS and US FDA Crystal City VI workshop on bioanalytical method validation for biomarkers. (February 2016) - Lowes, Steve; Ackermann, Bradley L
Crystal City VI Workshop on Bioanalytical Method Validation of Biomarkers, Renaissance Baltimore Harborplace Hotel, Baltimore, MD, USA, 28–29 September 2015 The Crystal City VI workshop was organized by the American Association of Pharmaceutical Scientists in association with the US FDA to continue discussion on the bioanalysis of biomarkers. An outcome of the Crystal City V workshop, convened following release of the draft FDA Guidance for Industry on Bioanalytical Methods Validation in 2013 was the need to have further discussion on biomarker methods. Biomarkers ultimately became the sole focal point for Crystal City VI, a meeting attended by approximately 200 people and composed of industry scientists and regulators from around the world. The meeting format included several panel discussions to maximize the opportunity for dialogue among participants. Following an initial session on the general topic of biomarker assays and intended use, more focused sessions were held on chromatographic (LC–MS) and ligand-binding assays. In addition to participation by the drug development community, significant representation was present from clinical testing laboratories. The experience of this latter group, collectively identified as practitioners of CLIA (Clinical Laboratory Improvement Amendments), helped shape the discussion and takeaways from the meeting. While the need to operate within the framework of the current BMV guidance was clearly acknowledged, a general understanding that biomarker methods validation cannot be adequately depicted by current PK-centric guidelines emerged as a consensus from the meeting. This report is not intended to constitute the official proceedings from Crystal City VI, which is expected to be published in early 2016.